An Investigation of the Intentional Communication and Symbolic Play Skills of Children With Down Syndrome and Cerebral Palsy in Malaysia. (June 2014) - Joginder Singh, Susheel; Iacono, Teresa; Gray, Kylie M.
Children with Down syndrome (DS) and cerebral palsy (CP) are at risk of remaining pre-symbolic in their communication and play for prolonged periods. The aim of this study was to explore the early communication and play of children with DS and with CP who communicated at the pre-symbolic stage, and to determine the association between these skills. This study was conducted in Malaysia. Twelve children with DS and 12 with CP who met the criterion of demonstrating pre-symbolic communication were observed during interaction with their mothers and siblings, and the interactions were coded for the children's communicative behaviors and play. The children were observed to communicate using pre-symbolic modalities most accessible to them. The children with DS demonstrated more communicative behaviors (intentional communicative acts and pre-intentional communicative acts) compared with children with CP. Participants produced little or no symbolic play, showing a preference for functional play instead. The symbolic play of the children with DS was negatively associated with their pre-symbolic intentional communicative acts, suggesting that both skills need to be targeted in intervention aimed at transitioning them to symbolic communication. The physical limitations of children with CP limited their demonstration of communicative behaviors and play.